Surface EMG of the masticatory muscles (part 4): Effects of occlusal splints and other treatment modalities = Oberflächen-EMG der Kaumuskulatur (Teil 4): Wirkung von Okklusionsschienen und anderen therapeutischen Maßnahmen - Hugger, Sybille; Schindler, Hans J.; Kordaß, Bernd; Hugger, Alfons (International journal of computerized dentistry, 2013)
The fourth part of this literature review on the clinical relevance of surface electromyography (EMG) of the masticatory muscles summarizes the results of clinical studies in patients with temporomandibular disorders (TMD), preferably randomized controlled trials, examining the impact of changes to the dynamic occlusion or the effects of occlusal splints and other treatment measures on electromyographic activity. Surface electromyography is a useful tool for neuromuscular functional analysis in the field of dentistry. In combination with a thorough history and detailed clinical examination, it is able to provide objective, documentable, valid and reproducible information about the individual functional status of the masticatory muscles if the user strictly adheres to the specific guidelines.
Gesehen am 07.12.2021